Al-Qard Sebagai Penerapan Akad Tabarru’ - Muna, Khairatun (Department of Islamic Economic Law, Faculty of Sharia, Sultanah Nahrasiyah State Islamic University, Lhokseumawe, 2022)
In principle, a tabbaru contract is a contract that aims to give something or lend something, where this if the contract is to lend something, the object can be in the form of money or services. Although in its basic provisions the borrower is prohibited from taking advantage of the tabbaru contract considering that it is usury, but the borrower can still receive kindness from other parties in the form of costs which have been incurred for the tabbaru contract, provided that they are not allowed to take profit even though with a small nominal, the case is different from giving the borrower itself outside the provisions at the time of the contract.